Inventory Optimization Analysis Using the Economic Order Quantity (EOQ) Method at Pabrik Kerupuk Citra - Irna Maya Sari; Rismawati Rismawati (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the optimization of raw material inventory at the home industry Pabrik Kerupuk Citra, focusing on the optimization of Economic Order Quantity (EOQ), safety stock, lead time, and reorder point during the 2022 to 2024 period. The data used include annual demand, ordering costs, and holding costs, with the assumption of a three-day lead time and a 95% service level. The calculation results show that EOQ values increased each year, amounting to 1,837 kg in 2022, 1,673 kg in 2023, and 1,722 kg in 2024. This increase reflects adjustments to the dynamics of costs and raw material needs. In addition, safety stock also rose from 77.9 kg (2022) to 82.6 kg (2024), in line with the growth in daily demand. Nevertheless, the short lead time allows the company to maintain inventory efficiency with an optimal level of security. The reorder point was calculated proportionally to the raw material requirements, highlighting the importance of a timely reordering system. This study concludes that implementing the EOQ method integrated with the management of safety stock and reorder point can improve inventory cost efficiency and ensure a smooth production process. Strategic recommendations include regular monitoring of cost variables, demand, and delivery accuracy, as well as the implementation of an automated inventory control system.